REDEFINING URBAN IDENTITY THROUGH CONTEMPORARY IBAN TATTOO CULTURE IN SARAWAK - Ringah, Kanyan; Musdi, Shanat; Jameel, Muhammad Kamil; Tarmiji, Masron; Daniel Ugih, Echoh; Rebecca Constance, Richard (Universiti Malaysia Sabah (UMS), 2025)
This study examines the resurgence and evolving significance of Iban tattoo practices among urbanised Iban communities in Sarawak, focusing on their role in preserving cultural heritage and shaping contemporary urban identities. Once integral to Iban spiritual and social practices, the tradition of Iban tattoos declined with the onset of modernisation, shifts in religious beliefs, and economic changes. Recently, however, a resurgence has gained momentum, largely driven by urban Iban youth who seek to reconnect with their heritage while integrating traditional tattoo motifs into contemporary aesthetics. Through ethnographic observations at international tattoo festivals across Sarawak between April and November 2024, alongside in-depth interviews with tattoo artists and cultural advocates, this research examines the transformation of Iban tattoos from ancestral symbols to expressions of modern identity. The findings underscore three key themes—heritage preservation, aesthetic adaptation, and identity reformation—that redefine the role of Iban tattoos in today’s urban culture. This study contributes to understanding the resilience of urbanised Iban identity and the ways in which cultural heritage is integrated into a globalised urban lifestyle.